Identity Formation in the Stories of Ivana Brlić-Mažuranić (Training and Practice : Journal of Educational Sciences, 2018)
Identities of male and female characters in the stories of Ivana Brlić-Mažuranić are formed on a male-female binary opposition. The authors explain this thesis by analysing the leading male and female characters in the stories of Fisherman Plunk and His Wife (Ribar Palunko i njegova žena) and Stribor's Forest (Šuma Striborova). Despite the predominance of the patriarchal model in the social context, the authors point to the distinction between women's activity and courage and the passivity and naivety of male characters. The stories show a gradual evolution of the male protagonists, influenced by female persistence, motherhood, as well as parenthood. The development of the characters mentioned above goes hand in hand with the motif of travel, as a metaphor of life, during which a thorough transformation of the patterns of behaviour and the system of values of the male characters occur.